2009
DOI: 10.1515/jgt.2008.070
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic (2, 2)-transformation groups

Abstract: Abstract. In this paper we determine all algebraic transformation groups G, defined over an algebraically closed field k, which operate transitively, but not primitively, on a variety W, subject to the following conditions. We require that the (non-e¤ective) action of G on the variety of blocks is sharply 2-transitive, as well as the action on a block D of the normalizer G D . Also we require sharp transitivity on pairs ðX ; Y Þ of independent points of W, i.e. points contained in di¤erent blocks.Although clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In the case i), as well as in the case ii), we have z = e 4 , e 6 , hence u = e 3 , e 5 , because elements not in e 3 are automorphisms of the Lie algebra given in the claim. Moreover, since there are two linearly independent vectors in n which are fixed by K, this vectors must be e 3 and e 4 , hence the above one is the only possible action.…”
Section: Proposition 32 Letmentioning
confidence: 93%
See 2 more Smart Citations
“…In the case i), as well as in the case ii), we have z = e 4 , e 6 , hence u = e 3 , e 5 , because elements not in e 3 are automorphisms of the Lie algebra given in the claim. Moreover, since there are two linearly independent vectors in n which are fixed by K, this vectors must be e 3 and e 4 , hence the above one is the only possible action.…”
Section: Proposition 32 Letmentioning
confidence: 93%
“…Although for algebraic groups over an algebraically closed field any sharply 2-transitive group is isomorphic to the group of affine mappings of the line, in the case of positive characteristic there are many imprimitive algebraic groups acting sharply 2-transitively on the system of blocks as well as on any block, as it is shown in [3]. This is essentially due to the existence of the Frobenius automorphism.…”
Section: II §6)mentioning
confidence: 99%
See 1 more Smart Citation
“…As the manuscript was growing, the young collaborators began to feel the necessity of proving their work with a publication, thus in 2004 (sic!) they came out with the first one [1], and, after five years, with a second one [2]. In the first one, they showed that the case where m > 2 has only few cases.…”
Section: Karl's Work In Palermomentioning
confidence: 96%
“…Thus, the investigation can be confined to the case of what we called a (2, 2)-group, which can be illustrated as follows: let Ω be a set operated on imprimitively by a group G, in such a way that the stabilizer G Δ of a block Δ acts sharply 2-transitive on Δ, that G/N is sharply 2-transitive on the system of imprimitivity Ω, that is, the set of blocks, where N is the inertia group, that is, the normal subgroup that leaves each block invariant, and, finally, that G is sharply transitive on the set Λ := {(P 1 , P 2 ) ∈ Ω 2 : Δ P1 = Δ P2 }. Algebraic (2, 2)-transformation groups had been characterized in 2009 [2]. In this paper, they exhibit an interesting class of examples where the group G has a non-Abelian, regular, subgroup T of translations: for an algebraically closed field k of characteristic p > 0, this group is defined on the set (k + ) 3 k * by the 1. there is one family of four-dimensional groups, parametrized by a nonzero real number s, which give deformations of the group of affine mappings over the dual numbers over R, which is obtained for s = 1; 2. there is one family of eight-dimensional groups, parametrized by a real number s and an integer number n ≥ 0, and for s = n = 1 one obtains the group of affine mappings of the affine line over the algebra of dual numbers over the complex field.…”
Section: Karl's Work In Palermomentioning
confidence: 99%